Studi Microgrid System Menuju Pembangunan Desa Mandiri Energi Di Desa Temajuk Kabupaten Sambas - Yunando, Yunando; Sutriyatna, Sutriyatna (Faculty of Engineering, Universitas Tanjungpura, 2018)
Abstractâ€“ Temajuk Village is one of the villages in Kecamatan Paloh Sambas regency, West Kalimantan Province, which borders directly with Sarawak (Malaysia). From 1980 to 2011 Desa Temajuk has no permanent electricity yet. In 2011, the village will have electrical energy by utilizing local energy such as Micro Hydro Power Generation, by 2012, Centralized Solar Power Generation and by 2015 Diesel Power Plant, all of which will carry each load without being integrated with the same network . So it is necessary to do the study of merging a network that is connected to one another to be able to bear the same load.Microgrid System study was then created with the aim of producing a sustainable distribution network study by combining 3 different types of plants and operational savings from the use of diesel fuel oil costs as the main power plant after the network system.Â Keywords- Microgrid System, cost savings